2017
DOI: 10.1021/acs.jpcc.7b07125
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Adsorbates on Calcite and Quartz Surfaces Investigated by NMR Spectroscopy

Abstract: The research presented here is part of a larger research project named "Wetting in porous media, a multi method approach to measurement, imaging and modelling". The main focus in papers 1-4 has been to study mechanisms responsible for wettability alteration on reservoir minerals and then to study how surface wettability affects the distribution of immiscible fluids in porous media. Nuclear Magnetic Resonance (NMR) has been the main analytical tool. The thesis consists of two parts. Chapters 1-5 contains an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…In a recent study, Ataman et al demonstrated, using density functional theory (DFT) and XPS in a study with pure calcite, that carboxylate interacts more strongly with calcite than alcohols, water and aldehydes, and that the presence of side groups on these molecules influences their adsorption behavior. Our results are in excellent agreement with that work and with the results of a more recent NMR investigation of crude oil adsorbates on calcite, where carboxylate adsorption was demonstrated to be responsible for wettability alteration …”
Section: Resultssupporting
confidence: 92%
“…In a recent study, Ataman et al demonstrated, using density functional theory (DFT) and XPS in a study with pure calcite, that carboxylate interacts more strongly with calcite than alcohols, water and aldehydes, and that the presence of side groups on these molecules influences their adsorption behavior. Our results are in excellent agreement with that work and with the results of a more recent NMR investigation of crude oil adsorbates on calcite, where carboxylate adsorption was demonstrated to be responsible for wettability alteration …”
Section: Resultssupporting
confidence: 92%
“…MD simulations confirmed that alcohols with molecular mass greater than that of methanol could displace water at the calcite surface [49,50]. Also, recent experiments showed that organic acids adsorb directly onto the calcite surface [51]. In the oil-wet initial state, since oil contacts the calcite surface, ions solvated in brine do not necessarily contact the oil phase (see the schematic diagram in Fig.…”
Section: Theory and Methodsmentioning
confidence: 80%
“…A principal surface-active material within the crude oil phase has been reported to be asphaltenes that can diffuse into the oil/water interface and form a rigid solid-like interface. , Formation of a rigid interfacial film by asphaltenes at the oil/water interface has been recognised as the main mechanism of stable water in crude oil (W/O) emulsions. Also, asphaltenes can diffuse into the oil/water interface and decrease the oil/water interfacial tension through interacting with the water molecules. , Carboxylic acids are distinctive surface-active materials inside the crude oil with the ability to diffuse into the oil/water interface and decrease the interfacial tension. , Formation of the lamellar liquid crystalline phase at the oil/water interface has been suggested as the mechanism of stable W/O emulsions by carboxylic acids. Moreover, asphaltenes and carboxylic acids were reported as the main compounds of crude oils affecting the initial wettability state of the oil reservoirs after the migration of the oil from the source rock. Thus, proposing methods to remove these surface-active materials (asphaltenes and carboxylic acids) from the rock surface leading to wettability improvement would be desirable, as it would improve oil recovery.…”
Section: Introductionmentioning
confidence: 99%